Incidence of medically attended paediatric burns across the UK. Issue 1 (21st February 2019) - Davies, Katie; Johnson, Emma Louise; Hollén, Linda; Jones, Hywel M; Lyttle, Mark D; Maguire, Sabine; Kemp, Alison Mary
Abstract : Objective: Childhood burns represent a burden on health services, yet the full extent of the problem is difficult to quantify. We estimated the annual UK incidence from primary care (PC), emergency attendances (EA), hospital admissions (HA) and deaths. Methods: The population was children (0–15 years), across England, Wales, Scotland and Northern Ireland (NI), with medically attended burns 2013–2015. Routinely collected data sources included PC attendances from Clinical Practice Research Datalink 2013–2015), EAs from Paediatric Emergency Research in the United Kingdom and Ireland (PERUKI, 2014) and National Health Services Wales Informatics Services, HAs from Hospital Episode Statistics, National Services Scotland and Social Services and Public Safety (2014), and mortality from the Office for National Statistics, National Records of Scotland and NI Statistics and Research Agency 2013–2015. The population denominators were based on Office for National Statistics mid-year population estimates. Results: The annual PC burns attendance was 16.1/10 000 persons at risk (95% CI 15.6 to 16.6); EAs were 35.1/10 000 persons at risk (95% CI 34.7 to 35.5) in England and 28.9 (95% CI 27.5 to 30.3) in Wales. HAs ranged from 6.0/10 000 person at risk (95% CI 5.9 to 6.2) in England to 3.1 in Wales and Scotland (95% CI 2.7 to 3.8 and 2.7 to 3.5, respectively) and 2.8 (95% CI 2.4 to 3.4) in NI. In England, Wales and Scotland, 75% of HAs were aged <5 years. Mortality was low with 0.1/1 000 000 persons at risk (95% CI 0.06 to 0.2). Conclusions: With an estimated 19 574 PC attendances, 37 703 EAs (England and Wales only), 6639 HAs and 1–6 childhood deaths annually, there is an urgent need to improve UK childhood burns prevention.